Draft Eighth Five year Plan 1990-95 Volume : XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1990)
The Health plan was formulated with the objectives of providing a package of health care services consisting of curative, promotive, preventive, Maternity and Child health, Immunisation, Nutrition and Family Planning.
Government of Assam, Development Commissioner for Hill Areas